La maison longue Imaha II revisitée : analyse tracéologique de l'outillage en quartzite de Ramah - Paquin, Simon (Université Laval, 2016)
The emergence of the longhouse during the Late Dorset period (ca 1500 years BP), exceptional by their dimensions and shape in comparison with paleoeskimo architectural traditions, is still somewhat misunderstood by archaeologists. Socioeconomic, ritual and symbolic causes have been suggested as explanation. Yet, the only view making consensus as of now portrays these longhouses as seasonal gathering sites where trades, festivities and ceremonies took place. This dissertation takes an interest in the activities that took place in these longhouses and in the form taken by these social gatherings. With this aim in mind, we employed the functional approach (use-wear analysis) to study lithic tools from the Imaha II longhouse on Nuvuarjuit island (Pamiok) in Nunavik. It was the first Dorset longhouse ever discovered in Arctic. However, its initial interpretation relating to a Norse presence in Ungava is known today to be incorrect. By putting in practice a modern method of analysis to study Imaha II this dissertation contributes to the restoration of the Imaha site scientific value. This research was also the opportunity to create a use-wear experimental frame of reference for the Ramah quartzite which is an emblematic raw material of the Labrador and oriental Arctic archaeology. In regard to this frame of reference, diagnostic use-wear patterns were observed and described for the tested functions. And, on the basis of these experimentations, some Ramah quartzite tools from Imaha II were analyzed and it has been possible to determine their functions. Then, a spatial analysis of these data was undertaken and allowed the suggestion of some hypothesis concerning activity organization in the house and social structuration of space. Keywords : Dorset, use-wear analysis, experimental archaeology, Ramah, lithic analysis, Paleoeskimo period, quatzite, Dorset longhouse, Nunavik. L’émergence des maisons longues au Dorsétien récent (ca 1500 ans AA), exceptionnelles en ce qui a trait à leur taille et leur forme par rapport aux ...